DevOps in practice breaking down traditional silos and building collaborative teams - Allspaw, John (O'Reilly Media, 2014)
"This unique collection demonstrates the essence of DevOps principles with practical, real-world examples of people and organizations putting them into practice. Ideal for system administrators, operations managers, and developers, each segment features a session from our recent Velocity conferences."--Resource description page.